PENERAPAN DISCRETE COSINE TRANSFORM (DCT) TERHADAP KOMPRESI CITRA DIGITAL - Bayu Dwi Raharja (Program Studi S1 Sistem Informasi Fakultas Komputer dan Teknik Universitas Alma Ata, 2021)
Image compression is a process that can reduce image size. In general, there are two types, lossless compression and loss compression. The method usually used in the JPEG standard is lossy compression, which removes some of the image information and takes advantage of the weakness in the insensitivity of the human eye in recognizing color gradations. With such large storage, data transfer or exchange is also increasingly difficult, especially data exchange using small storage areas. Tools that usually limit the size of storage for exchanging data. From the existing results using the DCT method is able to compress files up to 96%. Can be seen from the overall file average up to 74%